Komitmen Organisasi, Iklim Organiasi dan Disiplin Kerja terhadap Kinerja Karyawan - Yelta Triana Haloho; Henny Heriany Situmeang; Sofi Maulinda Mawaddah (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the partial influence of organizational commitment on employee performance, to determine the partial influence of organizational climate on employee performance, to determine the partial influence of work discipline on employee performance and to determine the partial influence of organizational commitment, organizational climate and work discipline simultaneous impact on employee performance at PT. Permata Berkat Jaya. The research approach used is quantitative, with associative research methods, data collection techniques using questionnaires and data analysis techniques using SPSS Version 23.0. The results of the research show that organizational commitment has a partial effect on employee performance, organizational climate has a partial effect on employee performance, organizational climate has a partial effect on employee performance, work discipline, and organizational commitment, organizational climate and work discipline have a simultaneous effect on employee performance. Keywords: Work Discipline, Climate, Organizational Commitment, Employee Performance